Observation of the Reconstitution Process and Factors that Influence the Final Condition of Chemotherapy Patients in Private Hospitals - Amelia, Kiki; Emilda, Tri (Poltekkes Kemenkes Tanjung Karang, 2024)
Handling of cytostatic preparations is the aseptic handling of cancer drugs in ready-to-use packaging according to patient needs by trained pharmacists with control of environmental safety, officers, and drug preparations from toxic effects and contamination, using personal protective equipment. Resistant to handling cytostatics preparations, including preparation, mixing, handling of spills, and cytostatics waste management. This study aimed to determine the suitability of the handling of cytostatic preparations and the description of the use of chemotherapy drugs in cancer patients. This research was conducted by descriptive analytic observation, data on the handling of cytostatics preparations was obtained by observing directly in the chemotherapy drug mixing room, and data on the use of chemotherapy drugs were obtained retrospectively by looking at medical records and service sheets of mixing cytostatics preparations The population and sample of cytostatic preparation handling are all cytostatic preparation reconstitution processes that can be directly observed during the research period, while the sample for evaluating the use of chemotherapy drugs is the medical records of patients undergoing chemotherapy in 2018. The results obtained in handling cytostatic preparations in the preparation, mixing, and labeling stages are 100% to the guidelines, while the labeling stage is 86% appropriate. Evaluation of the type of use of chemotherapy drugs is known that the taxane drug class is the most widely used by 91.7%. The proper assessment of chemotherapy drugs in breast cancer patients is 92%, lung cancer is 100%, and uterine cancer is 0%. Evaluation of the correct dose of chemotherapy drugs obtained results of 0%. The conclusion of the chi-square statistical test analysis of the chemical cycle affects the patient's condition.